2018
DOI: 10.1177/1470593118764590
|View full text |Cite
|
Sign up to set email alerts
|

Motivation: The missing driver for theorizing about resource integration

Abstract: Resource integration is vital to value co-creation. However, most research focuses on competencies as enablers of resource integration and the social aspects that guide them. Based on a literature review of resource integration and motivation theories, this article proposes including motivation as a driver of resource integration and integrating concepts from motivation theories into the resource integration process. This approach extends the understanding and conceptualization of actors' resource integration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 110 publications
(251 reference statements)
1
43
0
2
Order By: Relevance
“…[13], [32]. In addition, some of the articles also discuss the role actors play in the process of VCC and VCD and actors' motivations of engagement [23], [38], [39]. 12 papers discuss both resource integration and social interactions, mainly focus on their importance for value creation process.…”
Section: Conceptual Interpretativementioning
confidence: 99%
See 1 more Smart Citation
“…[13], [32]. In addition, some of the articles also discuss the role actors play in the process of VCC and VCD and actors' motivations of engagement [23], [38], [39]. 12 papers discuss both resource integration and social interactions, mainly focus on their importance for value creation process.…”
Section: Conceptual Interpretativementioning
confidence: 99%
“…Findsrud et al [38] identified motivation as vital factors of the explanation of how and why actors engage in the resource integration processes. Motivation is an important driver of activity, as it determines the direction (activities the actors choose to engage), intensity (efforts the actors put into the activities), and persistence of effort (continual engagement despite of negative experience) toward resource integration [38]. These factors also drive actors to participate in innovation projects and social interaction activities such as networking [46].…”
Section: Actors' Behavioral Driversmentioning
confidence: 99%
“…Câu hỏi đặt ra là tại sao có sự khác nhau về động cơ của mỗi người khi thực hiện việc tích hợp nguồn lực? Lược khảo lý thuyết cho thấy các nghiên cứu trước đây về đồng tạo sinh giá trị thường chỉ dừng lại ở việc xác định yếu tố động cơ của khách hàng là tiền tố tác động 7,8 . Tuy nhiên, tại sao có sự khác biệt về động cơ của khách hàng trong quá trình dịch vụ thì chưa được chỉ rõ.…”
Section: Giới Thiệuunclassified
“…Theo lý thuyết về sự sẵn lòng của khách hàng (customer readiness) 25,26 , động cơ là một tiền tố quan trọng ảnh hưởng đến hành vi của mỗi người và yếu tố động cơ được chỉ ra có tác động đến hành vi đồng tạo sinh của khách hàng 7,8 . Thêm vào đó, theo lý thuyết tự xác định, động cơ bên trong thúc đẩy mỗi người đạt được những chuẩn mực (được quy định bởi giá trị cá nhân của mỗi người), tạo nên cảm giác phấn chấn, cảm giác "tôi làm được" (self-efficacy) khi thực hiện thành công một việc nào đó 27 .…”
Section: độNg Cơ Bên Trong Và Sự Tham Gia Của Khách Hàngunclassified
“…The existing service discourse relies heavily on ideas such as value proposition and resource integration that often are taken for granted [2,3] despite seeming distant from operational realities in general and very far from realities of DSs in which automated services interact with each another. Also, an optimistic bias in the most widely cited articles that mention service science (see [4 p. 2]) sometimes is reflected in definitions that include aspirations not achieved in many real world situations, e.g., win-win, creating mutual value, balancing risk-taking and value cocreation, achieving and maintaining sustainable competitive advantage, and satisfying all relevant participants over time.…”
Section: Introductionmentioning
confidence: 99%